2000
DOI: 10.1002/1521-1878(200007)22:7<616::aid-bies4>3.3.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Six family genes—structure and function as transcription factors and their roles in development

Abstract: The members of the Six gene family were identified as homologues of Drosophila sine oculis which is essential for compound-eye formation. The Six proteins are characterized by the Six domain and the Six-type homeodomain, both of which are essential for specific DNA binding and for cooperative interactions with Eya proteins. Mammals possess six Six genes which can be subdivided into three subclasses, and mutations of Six genes have been identified in human genetic disorders. Characterization of Six genes from v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
173
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(182 citation statements)
references
References 0 publications
8
173
0
1
Order By: Relevance
“…Immunocytochemistry of MCF7 cells transfected with these Six1 deletion mutants demonstrated that similar to full-length Six1, DHD and DCterm were primarily nuclear, whereas DNterm was largely relocalized to the cytoplasm ( Figure 5). This observation corroborates recent findings that the nuclear localization sequence (NLS) of Six2, whose N-terminus is 93% conserved to that of Six1 (Kawakami et al, 2000), resides in the N-terminus of the protein (Brodbeck et al, 2004). The DNterm construct was therefore redesigned with an NLS (NLSDNterm) and nuclear expression in MCF7 cells confirmed by immunocytochemistry (data not shown).…”
Section: Six1 Is Degraded Via the Apc In Conjunction With Cdh1supporting
confidence: 87%
“…Immunocytochemistry of MCF7 cells transfected with these Six1 deletion mutants demonstrated that similar to full-length Six1, DHD and DCterm were primarily nuclear, whereas DNterm was largely relocalized to the cytoplasm ( Figure 5). This observation corroborates recent findings that the nuclear localization sequence (NLS) of Six2, whose N-terminus is 93% conserved to that of Six1 (Kawakami et al, 2000), resides in the N-terminus of the protein (Brodbeck et al, 2004). The DNterm construct was therefore redesigned with an NLS (NLSDNterm) and nuclear expression in MCF7 cells confirmed by immunocytochemistry (data not shown).…”
Section: Six1 Is Degraded Via the Apc In Conjunction With Cdh1supporting
confidence: 87%
“…The Six gene family was identified as a homologue of the Drosophila sine oculis (so) and is conserved in various species (Seo et al, 1999;Kawakami et al, 2000). Six gene products are characterized by the Six domain and Six-type homeodomain, which are required for specific DNA binding activity and function as transcription factors (Kawakami et al, 1996;Spitz et al, 1998;Ohto et al, 1999;Li et al, 2002;Lagutin et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Six gene products are characterized by the Six domain and Six-type homeodomain, which are required for specific DNA binding activity and function as transcription factors (Kawakami et al, 1996;Spitz et al, 1998;Ohto et al, 1999;Li et al, 2002;Lagutin et al, 2003). At present, six members of the family have been identified in mammals, and all members show a spatiotemporally regulated pattern of expression during embryogenesis, suggesting their involvement in embryonic development (Seo et al, 1999;Kawakami et al, 2000). The Six gene family is known to function as a component of the Pax-Six-Eya-Dach gene network.…”
Section: Introductionmentioning
confidence: 99%
“…The eyeless, sine oculis, eyes absent, and dachshund genes are required for normal eye development, and ectopic expression of eyeless, eyes absent, and dachshund induce ectopic eye formation. This regulatory pathway, conserved among metazoans and the vertebrate homologues of eyeless (Pax6), sine oculis (Six1-6), eyes absent (Eya1-4), and dachshund (DACH1-2), contributes to organism development (Kawakami et al, 2000). The six genes encode a conserved Six and Homeo domain sequencespecific DNA binding family of transcription factors.…”
Section: Introductionmentioning
confidence: 99%